Angiomyolipoma in the Transplanted Kidney Presenting with Hematuria- Rare Case Report (Bangladesh Journal of Nuclear Medicine, 2022)
Renal angiomyolipomas (AML) are a type of benign renal neoplasm composed of vascular, smooth muscle, and fat elements, usually exhibiting characteristic radiographic appearances. Although benign, they carry the risk of spontaneous hemorrhage, which can potentially be fatal. AML has an incidence of 0.3% to 3%, hence reports of this condition are relatively scarce; even more so is the unique presentation of AML in the transplanted kidney. Predictably, there have been few reports of this uncommon condition in the medical literature. Herein, we report a very rare case of an isolated AML in a transplanted kidney that developed more than a decade after uneventful renal transplantation.A 56-year-old female had a kidney transplant in early 2010, but subsequently developed chronic graft rejection. She presented with haematuria, and upon further assessment, a fairly large SOL in the kidney allograft was revealed by imaging including abdominal ultrasound, a 99mTc-DMSA scan, and a CT scan. She had graft nephrectomy in early 2022 and is still on haemodialysis. Bangladesh J. Nuclear Med. 25(2): 154-156, 2022